The Influence of Perceived Risk Factors on Online Purchase Intention among Millennials in Malaysia - Mahbob, Nur Nadiah; Hasim, Muhammad Asyraf; Ishak, Mohd Fikri (Information Management and Business Review, 2023)
This study investigates perceived risk factors that influence online purchase intention among Millennials in Malaysia. The study examined several predictor variables, namely financial risks, product risks, and non-delivery risks, whereas the result variable under investigation was online purchase intention. The study employs structured questionnaires verified for data collection through face and content validity. The data were analyzed using descriptive statistics through the Statistical Package for Social Sciences (SPSS) version 23. Multiple regression analysis was conducted to ascertain the association between the predictor factors and the outcome variable. The findings indicate a significant relationship between the predictor variables, namely financial risks, product risks, and non-delivery risks, and the outcome variable. The analysis shows that non-return risks exhibited the highest association with online purchase intention. The findings of this study offer significant contributions to the advancement of future research and the enhancement of online entrepreneurs’ ability to optimize their online operations and give enhanced consumer value experiences.